Multicomponent Domino [4+1+1] Carbocyclization Providing an Efficient and Regioselective Strategy to Fluoren‐9‐ones. Issue 6 (29th May 2013) - Li, Ying; Xu, Haiwei; Fu, Liping; Shi, Qingqing; Jiang, Bo; Tu, Shujiang
Abstract Concise and efficient three‐component domino [4+1+1] carbocyclization to highly substituted fluoren‐9‐one derivatives promoted by K2CO3 has been developed under microwave irradiation conditions. The direct bis‐cyanation and aryl amination residing in fluoren‐9‐one framework were achieved in a one‐pot operation. The reaction proceeds at fast rates and can be finished within 30 min, which makes workup convenient to give good to excellent chemical yields.